2016
DOI: 10.1515/nuka-2016-0045
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the influence of chamber construction parameters on radon exhalation rate

Abstract: Radon exhalation from ground is a process dependent on the emanation and migration of radon through ambient air. Most studies on radon exhalation from soil were performed regarding the influence of meteorological and soil parameters. As radon exhalation rate can be affected by the internal properties of the sample, it may also be influenced by the exhalation chamber geometry such as volume-to-area (V/S) ratio or other construction parameters. The measurements of radon exhalation from soil were made using diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The results of these comparative experiments have proved the consistency of 222 Rn activity concentration measurements conducted at several most important laboratories in the country [40,53,54]. Some research teams have also developed their own analytical and measurement methods, often based on research devices and test stands with unique structures [55][56][57][58][59][60][61][62][63][64][65][66][67].…”
Section: Measurement Techniquesmentioning
confidence: 90%
“…The results of these comparative experiments have proved the consistency of 222 Rn activity concentration measurements conducted at several most important laboratories in the country [40,53,54]. Some research teams have also developed their own analytical and measurement methods, often based on research devices and test stands with unique structures [55][56][57][58][59][60][61][62][63][64][65][66][67].…”
Section: Measurement Techniquesmentioning
confidence: 90%
“…In radon measurements, an active-type radon monitor is generally used for an accurate measurement or a short-term survey. However, some researchers have reported that the measured radon concentration would have been influenced by the existence of thoron [12][13][14]. For thoron measurements, an electrostatic collection radon-thoron monitor, namely RAD7, has been used by many researchers [15][16][17].…”
Section: Introductionmentioning
confidence: 99%